Teacher’s Perceptions of Using an Artificial Intelligence-Based Educational Tool for Scientific Writing - Kim, Nam Ju; Kim, Min Kyu (Frontiers in Education, 2022)
Efforts have constantly been made to incorporate AI into teaching and learning; however, the successful implementation of new instructional technologies is closely related to the attitudes of the teachers who lead the lesson. Teachers’ perceptions of AI utilization have only been investigated by only few scholars due an overall lack of experience of teachers regarding how AI can be utilized in the classroom as well as no specific idea of what AI-adopted tools would be like. This study investigated how teachers perceived an AI-enhanced scaffolding system developed to support students’ scientific writing for STEM education. Results revealed that most STEM teachers positively experienced AI as a source for superior scaffolding. On the other hand, they also raised the possibility of several issues caused by using AI such as the change in the role played by the teachers in the classroom and the transparency of the decisions made by the AI system. These results can be used as a foundation for which to create guidelines for the future integration of AI with STEM education in schools, since it reports teachers’ experiences utilizing the system and various considerations regarding its implementation.